Efficiency and Productivity of Zakat Management Organization Before and During Pandemic Covid-19 - Ninda Ardiani; Fitri Nur Latifah; Satrio Sudarso; Nuris Tiswanah (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the efficiency and productivity of zakat institutions in Indonesia before and during the Covid-19 pandemic using Data Envelopment Analysis (DEA) and the Malmquist Productivity Index (MPI). Our findings reveal that three out of the five zakat institutions exhibited efficiency at different periods. Notably, LAZ Al Azhar demonstrated consistent efficiency both before and during the pandemic, while LAZISNU was efficient in 2019-2020 but experienced inefficiency in 2021. Additionally, LAZ Rumah Zakat exhibited an increase in efficiency in 2020 but regressed to inefficiency in 2021, primarily attributed to excessive distribution of ZIS funds in each institution. These findings highlight the urgent need for standardization and optimization of zakat management to unlock its immense potential for equitable distribution and impact during times of crisis, offering valuable insights for policymakers and zakat institutions globally. Highlights: Standardization and Optimization: The absence of standardized zakat management contributes to suboptimal collection and distribution of zakat funds in Indonesia. DEA and MPI Analysis: Data Envelopment Analysis (DEA) and the Malmquist Productivity Index (MPI) serve as effective methods to evaluate the operational efficiency and productivity of zakat institutions. Implications for Global Zakat Institutions: Understanding the dynamics of zakat efficiency during crises can offer valuable insights for similar institutions worldwide to enhance their distribution impact and resource management. Keywords: Zakat institutions, Efficiency, Productivity, Indonesia, Covid-19 pandemic.